2017
DOI: 10.1089/gtmb.2017.0124
|View full text |Cite
|
Sign up to set email alerts
|

MTRR A66G, RFC1 G80A, and MTHFR C677T and A1298C Polymorphisms and Disease Activity in Mexicans with Rheumatoid Arthritis Treated with Methotrexate

Abstract: Aim: To investigate the relationships of polymorphisms in genes whose protein products are related in the metabolic pathway of folic acid, particularly MTRR A66G, RFC1 G80A, and MTHFR C677T and A1298C, and disease activity in Mexican patients with rheumatoid arthritis (RA) treated with methotrexate (MTX).Materials and Methods: Sixty-eight patients with RA were included in the study who were being treated with MTX, either with or without other drugs. In addition to general data, disease activity was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
(43 reference statements)
2
6
2
Order By: Relevance
“…In the present study, we detected no difference in genotypes and allele frequencies of MTHFR C677T and A1298C and RFC-1 A80G between patients with RA (cases) and controls, indicating that these polymorphisms were not associated with RA susceptibility in the Henan Han population, consistent with the results of Gonzalez-Mercado et al. 15 and Hashiguchi et al. 16 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we detected no difference in genotypes and allele frequencies of MTHFR C677T and A1298C and RFC-1 A80G between patients with RA (cases) and controls, indicating that these polymorphisms were not associated with RA susceptibility in the Henan Han population, consistent with the results of Gonzalez-Mercado et al. 15 and Hashiguchi et al. 16 …”
Section: Discussionsupporting
confidence: 92%
“…However, few studies have examined the relationship between RFC-1 SNP and RA. In the present study, we detected no difference in genotypes and allele frequencies of MTHFR C677T and A1298C and RFC-1 A80G between patients with RA (cases) and controls, indicating that these polymorphisms were not associated with RA susceptibility in the Henan Han population, consistent with the results of Gonzalez-Mercado et al 15 and Hashiguchi et al 16 MTX, as a DMARD, is the first-line anchor drug for treating RA. It plays a role in the folate transport pathway by inhibiting the key enzymes.…”
Section: Discussionsupporting
confidence: 91%
“…Two of the most investigated polymorphisms within the MTHFR gene are single nucleotide polymorphisms (SNPs) at the mRNA positions 677 (rs1801133) and 1,298 (rs1801131) ( 8 ). However, these findings were mainly found in the patients with rheumatoid arthritis or the hematological malignancies ( 14 16 , 27 ). This is the first report on serious adverse toxic effects of LD-MTX on an EP patient with MTHFR mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, no associations between the MTRR and MTR gene polymorphisms and good clinical responses were found in recent-onset RA patients ( Wessels et al, 2006 ). A study ( Gonzalez-Mercado et al, 2017 ) of 110 Mexican RA patients who were diagnosed at least 1 year previously and had been receiving MTX for at least 3 months showed no association between MTRR gene polymorphism and MTX efficacy. Another study ( Lopez-Rodriguez et al, 2018 ) of European Caucasian RA patients showed that MTRR fulfilled the high association standards.…”
Section: Discussionmentioning
confidence: 99%